THE DIFFERENCES BETWEEN MAINSTREAM AND SPECIAL EDUCATION (Annual of the Faculty of Philosophy in Skopje, 2024)
Inclusive education is a process that integrates students with special needs inmainstream schools, providing them with appropriate support and adaptations. Thispaper discusses the differences between mainstream and special education, focusing onthe right to education, aims and approaches, responsibilities and competences, curricula,focus of education, teacher preparation, learning conditions, teaching methods, learningstandards, assessment and evaluations, teacher competencies, educational researchand legislation. In Macedonia, inclusive education started in 1998 and is still in theprocess of development, aimed at the full inclusion of students with disabilities, which isstipulated in the Law on Basic Education passed in 2019.The methodology includes an analysis of existing research and laws, as well as acomparative study of regular and special education. Data from relevant sources such asEuropean and national education agencies, UNICEF reports and laws on special educationwere used. This methodology enables a detailed overview of the current situationand challenges in inclusive education.The conclusion is that although significant efforts have been made for theintegration of students with special needs in mainstream schools, there are manychallenges that need to be overcome. Better support for teachers, more resources andfunding, and a change in attitudes of the society are needed. With appropriate measuresand policies, real inclusion and quality education for all students can be achieved.
Keywords: inclusive education; mainstream education; special education; individual education plan; low legislative